Nat enough - Scrivan, Maria (New York, NY : Graphix, an imprint of Scholastic, 2020)
"Natalie has never felt that she's enough--athletic enough, stylish enough, or talented enough. And on the first day of middle school, Natalie discovers that things are worse than she thought--now she's not even cool enough for her best friend, Lily! As Natalie tries to get her best friend back, she learns more about her true self and natural talents. If Natalie can focus on who she is rather than who she isn't, then she might realize she's more than enough, just the way she is"--Amazon.com.
Kirkus Review
School Library Journal
Kirkus Review, January 2020
School Library Journal, January 2020
3-6
Keywords: Friendship -- Comic books, strips, etc. -- Juvenile fiction; Humorous stories; Middle school students -- Comic books, strips, etc. -- Juvenile fiction; Middle schools -- Comic books, strips, etc. -- Juvenile fiction; Self-esteem -- Comic books, strips, etc. -- Juvenile fiction; Cartoons and comics; Friendship -- Fiction; Humorous stories; Middle school students -- Fiction; Middle schools -- Fiction; Self-esteem -- Fiction; Friendship -- Comic books, strips, etc. -- Fiction; Humorous graphic novels; Middle school students -- Comic books, strips, etc. -- Fiction; Middle schools -- Comic, books, strips, etc. -- Fiction; Self-esteem -- Comic books, strips, etc. -- Fiction; Graphic novels; Humorous comics